Physical fitness and body composition in correlation with body weight of pupils in primary schools on the territory of the city of Skopje - Kodzoman К.; Gontarev S.; Shukova Stojmanovska D.; Krstevski B. (Faculty of physical education, sport and health, 2020)
The paper presents one segment of a research carried out in 2019 in 19 primary schools that was aimed to determine the fitness level of Macedonian adolescents of both genders with different values of body mass index (ИТМ). The paper focuses on the correlation between the physical fitness and body composition compared to the body weight of pupils from primary schools on the territory of the City of Skopje. The research was conducted on a sample of 4,051 adolescents, 2,078 boys and 1,973 girls. The respondents were divided in 4 categories: underweight, normal weight, overweight and obese. Total of 7 test of EUROFIT battery were applied and 5 anthropometric measurements were taken into consideration in accordance to the IBP methodology. The results obtained were statistically processed by SPSS, v. 16.0 for WINDOWS (variance analysis, covariance analysis, and χ2 test). The conclusion based on the obtained results is that young adolescents of both genders with moderate or high BMI have higher blood pressure; lower percentage of muscle mass; achieve poorer results in the relative strength, explosive strength, agility, and coordination tests; and have lower aerobic capacity.
Keywords: EUROFIT, IBP, young adolescents, City of Skopje